Biodiversity Loss and Its Impact on Ecosystem Services - Khan, Muhammad Shakeel; Asadullah, Hafiz Muhammad (ACADEMIA Biota Nexus Journal, 2025)
Biodiversity provides comfort and sustainability of the ecosystem because it provides the much needed services to maintain human operations. However, all these are being consumed at an extremely rapid rate with excessive use of natural resources, destruction of habitat, climate change, pollution and human activities leaving behind almost no biodiversity. The reduction of species richness and genetic diversity has direct effects to the ecosystem services which include the provision, regulation, cultural and supporting services that destabilize the ecological balance and sustenance of the human beings. The given paper ponders upon the sophisticated nature of the correlation between the loss of biodiversity and ecosystem services and the effect of species extinction on the ecosystem functioning. The argument is that it is necessary to have the practices of sustainable management and conservation strategies that can be in place to reduce the losses of biodiversity and preserve the ecosystem services that can be utilized by the future generations. These findings all have an implication of the significance of the biodiversity as it relates to the need to balance the ecosystem and socio economic consequences of the loss of the same.